Neutral lipid stores and lipase PNPLA5 contribute to autophagosome biogenesis - Dupont, Nicolas (2014)
BACKGROUND: Autophagy is a fundamental cell biological process whereby eukaryotic cells form membranes in the cytoplasm to sequester diverse intracellular targets. Although significant progress has been made in understanding the origins of autophagosomal organelles, the source of lipids that support autophagic membrane formation remain an important open question. RESULTS: Here we show that lipid droplets as cellular stores of neutral lipids including triglycerides contribute to autophagic initiation. Lipid droplets, as previously shown, were consumed upon induction of autophagy by starvation. However, inhibition of autophagic maturation by blocking acidification or using dominant negative Atg4(C74A) that prohibits autophagosomal closure, did not prevent disappearance of lipid droplets. Thus, lipid droplets continued to be utilized upon induction of autophagy but not as autophagic substrates in a process referred to as lipophagy. We considered an alternative model whereby lipid droplets were consumed not as a part of lipophagy but as a potential contributing source to the biogenesis of lipid precursors for nascent autophagosomes. We carried out a screen for a potential link between triglyceride mobilization and autophagy, and identified a neutral lipase, PNPLA5, as being required for efficient autophagy. PNPLA5, which localized to lipid droplets, was needed for optimal initiation of autophagy. PNPLA5 was required for autophagy of diverse substrates including degradation of autophagic adaptors, bulk proteolysis, mitochondrial quantity control, and microbial clearance. CONCLUSIONS: Lipid droplets contribute to autophagic capacity by enhancing it in a process dependent on PNPLA5. Thus, neutral lipid stores are mobilized during autophagy to support autophagic membrane formation.